COVID-19 and business renewal : Lessons and insights from the global airline industry - Amankwah-Amoah, Joseph; Khan, Zaheer; Osabutey, Ellis L.C. (Elsevier, 2021)
The emergence of the COVID-19 pandemic has adversely affected the fortunes of multiple companies around the globe. Accordingly, questions are increasingly being asked about how organizations can revitalize during and after a crisis. Yet, we have limited understanding of how organizations renew themselves during crises over time. We explore this question through the lens and examination of two South-Asian airlines: Pakistan International Airlines and Sri Lankan Airlines. The cases offer important insights into the reasons behind underperformance of state-controlled enterprises and renewal activities. We shed light on strategic renewal (SR) in the wake of increasing liberalization and deregulations in the global airline industry. To this end, we propose a four-stage approach towards renewing such underperforming organizations to respond effectively to black swan events and external shocks.
Keywords: emerging markets; External shocks; Pakistan; Sri Lanka; State-owned enterprises; Strategic renewal; COVID-19; airlines; fi=Kansainvälinen liiketoiminta|en=International Business|